2018
DOI: 10.1159/000493833
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid A Protects Against Oxidative Stress and Apoptosis Induced by Intestinal Ischemia-Reperfusion Injury Through Activation of Nrf2/HO-1 Pathways

Abstract: Background/Aims: Ischemia-reperfusion (I/R) adversely affects the intestinal mucosa. The major mechanisms of I/R are the generation of reactive oxygen species (ROS) and apoptosis. Salvianolic acid A (SalA) is suggested to be an effective antioxidative and antiapoptotic agent in numerous pathological injuries. The present study investigated the protective role of SalA in I/R of the intestine. Methods: Adult male Sprague-Dawley rats were subjected to intestinal I/R injury in vivo. In vitro experiments were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…That being so, whether OS preconditioning can also enhance anti‐OS ability of BMSCs, protect the survival of BMSCs under OS conditions? For the possible mechanism of antioxidant stress in cells, nuclear factor erythroid 2‐related factor 2 (Nrf2) is the most important and classical one among many signaling pathways . Nrf2 nuclear translocation, which promotes the expression of antioxidant enzymes genes, is essential for antioxidant stress …”
Section: Introductionmentioning
confidence: 99%
“…That being so, whether OS preconditioning can also enhance anti‐OS ability of BMSCs, protect the survival of BMSCs under OS conditions? For the possible mechanism of antioxidant stress in cells, nuclear factor erythroid 2‐related factor 2 (Nrf2) is the most important and classical one among many signaling pathways . Nrf2 nuclear translocation, which promotes the expression of antioxidant enzymes genes, is essential for antioxidant stress …”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, apoptosis and inflammation are important mechanisms associated with II/R injury. TUNEL staining is one major method to detect cell apoptosis, and pro‐inflammatory factors including IL‐1β, IL‐6, and TNF‐α can reflect inflammatory response (Y. Li, Wen, et al, ; Y. Li, Xu, et al, ; Zu, Zhou, Che, & Zhang, ). In this study, our results showed that the numbers of apoptotic cells and the mRNA levels of IL‐1β, IL‐6, and TNF‐α were significantly increased after 4 hr of hypoxia and 120 min of reoxygenation in IEC‐6 cells and ischaemia for 45 min and reperfusion for 90 min in mice compared with control group or sham group, which were reduced with the prolongation of reoxygenation or reperfusion time compared with 120 min of reoxygenation in vitro or reperfusion for 90 min in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the data in Li, Wen, et al, 2017;Y. Li, Xu, et al, 2017;Zu, Zhou, Che, & Zhang, 2018). In this study, our results showed that the numbers of apoptotic cells and the mRNA levels of IL-1β, IL-6, and TNF-α were significantly increased after 4 hr of hypoxia and 120 min of reoxygenation in IEC-6 cells and ischaemia for 45 min and reperfusion for 90 min in mice compared with control group or sham group, which were reduced with the prolongation of reoxygenation or reperfusion time compared with 120 min of reoxygenation in vitro or reperfusion for 90 min in vivo.…”
Section: Overexpression Of Mir-29b-3p Alleviated H/r-caused Injury mentioning
confidence: 98%
“…Hence, lPS-induced lung injury is always used to study gram-negative bacterial-associated lung injury (54). The protective mechanisms of deX on lung injury induced by iir or lPS may not exactly be the same, since the activation of the nrf2/Ho-1 pathway has been reported to decrease oxidation products and improve intestinal mucosal injury in an iir model (55). Ho-1 is also a stress-responsive enzyme that produces antioxidants and anti-inflammatory agents (56).…”
Section: Discussionmentioning
confidence: 99%